Identification of B6T173 (ZmPrx35) as the prevailing peroxidase in highly insect-resistant maize (Zea mays, p84C3) kernels by activity-directed purification - López-Castillo, Laura M.; López-Arciniega, Janet A. I.; Guerrero-Rangel, Armando; Valdés-Rodríguez, Silvia; Brieba, Luis G.; García-Lara, Silverio; Winkler, Robert (Frontiers in Plant Science, 2015)
Plant peroxidases (PODs) are involved in diverse physiological processes, including defence against pathogens and insects. Contrary to their biological importance, only very few plant peroxidases have been proven on protein level, because their low abundance makes them difficult to detect in standard proteomics work-flows. A statistically significant positive correlation between peroxidase activity and post-harvest insect resistance has been found for maize (Zea mays, p84C3) kernels. In combining activity-directed protein purification, genomic and proteomic tools we found that protein B6T173 (ZmPrx35) is responsible for the majority of the peroxidase activity of the kernel. We successfully produced recombinant ZmPrx35 protein in Escherichia coli and demonstrate both, in vitro activity and the presence of a haem (heme) cofactor of the enzyme. Our findings support the screening for insect resistant maize variants and the construction of genetically optimised maize plants.